Non-Cognitive Development in Early Childhood: The Influence of Maternal Employment and the Mediating Role of Childcare - McDonnell, Thérèse (The Economic and Social Review, 2016)
This study uses data on Irish pre-school children to examine the influence of maternal employment in infancy on children’s non-cognitive skills. Propensity score matching addresses the issue of potential selection bias and mediation analysis is used to investigate possible mechanisms for the effect of maternal employment, in particular the role of childcare, parental stress, quality of parent-child attachment and income. Effects are identified for children from less advantaged backgrounds, with full-time maternal employment in infancy having a significant and detrimental effect on non-cognitive development at three years old. This effect is primarily mediated by childcare choices, particularly unpaid grandparental arrangements.